Sensitive Skin Syndrome: A Low-Noise Small-Fiber Neuropathy Related to Environmental Factors? - Misery, Laurent; Bataille, Adeline; Talagas, Matthieu; Le Gall-Ianotto, Christelle; Fouchard, Maxime; Huet, Flavien; Ficheux, Anne-Sophie; Roudot, Alain-Claude; Fluhr, Joachim W.; Brenaut, Emilie (Frontiers in Pain Research, 2022)
Background and objectives: Patients frequently complain of mild, transient, unpleasant skin sensations that cannot be diagnosed as common neuropathies. Dermatologists have termed these symptoms “sensitive skin syndrome”. This narrative review was performed for a better knowledge by other specialists. Databases and data treatment: Publications on pain in sensitive skin syndrome were obtained from PubMed. Results: There is a growing body of data supporting the concept that sensitive skin is a type of small-fibre neuropathy. The arguments are based on clinical data, a decrease in intra-epidermal nerve fibre density, quantitative sensory testing abnormalities and an association with irritable bowel syndrome and sensitive eyes. Sensitive skin is triggered by environmental factors. Sensitive skin is a frequent condition, with a lifetime prevalence of approximately 50% according to self-reports. Conclusions: Mild levels of skin pain or itch are frequently experienced by patients, who rarely report them. There is a need for a better knowledge of sensitive skin because it can be the first level of small-fiber neuropathies.